2000
DOI: 10.1046/j.1440-1754.2000.00552.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastroschisis: Early enteral feeds may improve outcome

Abstract: Gastroschisis has a favourable outlook, with 89.7% survival of live births. Over the 10 year period studied, there has been a reduction in length of hospital stay and duration of TPN. The age at which the infant is first fed enteral feeds appears to be important in affecting the length of hospital stay and the duration of TPN, with delays associated with a longer hospital stay and longer TPN duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 30 publications
3
18
0
Order By: Relevance
“…Most of the patients with gastroschisis had low birth weights and were borderline premature, which is in agreement with the literature [14,17,20,21]. The gestational age of the study patients was significantly higher than that of NICU control subjects, whereas birth weights were similar, emphasizing the link between gastroschisis and growth retardation.…”
Section: Discussionsupporting
confidence: 91%
“…Most of the patients with gastroschisis had low birth weights and were borderline premature, which is in agreement with the literature [14,17,20,21]. The gestational age of the study patients was significantly higher than that of NICU control subjects, whereas birth weights were similar, emphasizing the link between gastroschisis and growth retardation.…”
Section: Discussionsupporting
confidence: 91%
“…19,20 Aljahdali et al 19 observed a better evolution when diets were initiated seven days after the abdominal wall closure. Sharp et al 20 found that for every day of delay of the start of enteral nutrition, there was an increase in the length of stay of 1.05 days and an increase in the duration of enteral nutrition of 1.06 days.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a spring-loaded silo followed by elective repair permits gentle gradual reduction of the viscera and, when compared to early primary repair, the spring-loaded silo was associated with significantly lower airway pressures, early extubation, fewer complications, and decreased length of stay and hospital charges [66]. Sharp et al [67] reported that the age at first enteral feeds was significantly related with the length of hospital stay and duration of total parenteral nutrition. The possible physiological reasons that account for the benefits of early enteral feeding include the presence of substances in the milk (glutamine, arginine, insulin-like growth factors) that are trophic to the gastrointestinal tract, development of gastrointestinal motor activity, or the release of trophic enteric hormones.…”
Section: Postnatal Outcomementioning
confidence: 99%
“…The long-term outcomes [63][64][65][66][67] are generally related to the degree of gastrointestinal compromise and the presence of gastrointestinal atresia. Approximately 10% of patients with gastroschisis will have hypoperistalsis syndrome.…”
Section: Postnatal Outcomementioning
confidence: 99%